An insight on archbishop Desmond Tutu’s struggle against apartheid in South Africa - Kokobili, Alexander (Array, 2019)
This article focuses of Archbishop Desmond Tutu’s role against the apartheid system of racism and socio-political inequality in the Republic of South Africa. Tutu often denounced apartheid in his speeches and public advocacy promoting equality, reconciliation, and peaceful coexistence of all South Africans. The ideology of apartheid robbed the black race in South Africa of their human dignity which contradicts the Holy Bible which states, “So God created man in His own image; in the image of God He created him; male and female He created them” (Genesis 1:27). Despite this, the white National Party of South Africa in 1948 legitimized apartheid as a political system and gained support from the Dutch Reformed Church despite its anti-Christian ethics. Apartheid was adopted to place the white minority in the upper class, while the black majority was left with fewer rights and fewer privileges in South Africa. Desmond Tutu was one of the few Christian leaders in Africa who championed the course for black theology in the demolition of apartheid in South Africa. Tutu’s attitude during the apartheid struggle was not by violent protest or riots but rather through his sermons and public participation in activities clamoring for national unity, love, and equality of all South Africans.